2-Chloro-5-nitropyridine - Ng, S.W. (International Union of Crystallography, 2010)
The non-H atoms of the title compound, C(5)H(3)ClN(2)O(2), almost lie in a common plane (r.m.s. deviation = 0.090 angstrom). In the crystal, adjacent molecules feature a short Cl center dot center dot center dot O contact [3.068 (4) angstrom], forming a chain; these chains are consolidated into a layer structure by non-classical C-H center dot center dot center dot O interactions.